Compositional and Rheological Properties of Mozzarella Cheese Prepared from Buffalo Milk - Mari, G.M.; Khaskheli, M.; Jatoi, A.S.; Qazi, I.H.; Samina, M.; Talpur, A.; Majeed, S.; Soomro, A.H.; Rukhsana, L.; Samad, A. (Pakistan Journal of Nutrition, 2014)
Mozzarella cheese was prepared from buffalo milk using liquid rennet extracted from calf stomach at the Laboratory of Animal Products Technology, Sindh Agriculture University Tandojam. All the cheese batches were evaluated for compositional, rheological and sensory characteristics. The mean moisture content of mozzarella cheese was 55.15±0.88%, whereas, protein, non protein nitrogen and fat content was 25.28±0.45, 1.56±0.07 and 15.69±0.29%, respectively. The average ash and chloride content was observed as 3.42±0.10 and 1.60±0.02%, respectively. The meltability and strechability of mozzarella cheese was observed as 6.11±0.16 and 12.75±0.15cm, respectively. The sensory attributes showed that color/appearance of mozzarella cheese perceived 4.10±0.27 score, the score for flavor of mozzarella cheese was 27.90±0.43 and the body/texture received 23.60 ±0.52 score. It was concluded that average moisture content of mozzarella cheese revealed that the product was under high moisture category cheese, regardless the fat, meltability and strechability concludes it to be used primarily as an ingredient for pizza making.